Northwest history. Mining. Report. 1929-04-21 (1929)
Bunker Hill big in other lands. - Its treadwell Yukon making large mines in Yukon, Ontario and Nevada. - Yukon nets $534,000. - With nevada, expected to become $1,500,000 yearly. - How the investment of the Bunker Hill & Sullivan Mining and Concentrating company outside of Idaho is enhancing in value is indicated by the report for 1928 of the Treadwell Yukon company, in which the Bunker Hill owns a half interest.